IS ASEAN’S PRACTICE OF NON-INTERFERENCE AND REGIONAL PARTICULARISM PRINCIPLES A SOURCE OF HINDRANCE FOR HUMAN RIGHTS LAW ENFORCEMENT IN SOUTH EAST ASIA? - Siti Rochmah Aga Desyana (International Law Department, Faculty of Law Universitas Padjadjaran, 2020)
Abstract In the ages of Duterte and his extrajudicial killing policies, of Aung Sang Suu Kyi and the Rohinya systemic persecution, of Malays rejecting the ratification of International Convention for Eradication of Racial Discrimination (ICERD), and other unfortunate events spanning across the region, South East Asia was largely suffering from various grave breaches of human rights violations. As the subcontinent umbrella organization, however, ASEAN’s hand has been largely tied when facing the issues pertaining in their region, despite pledging their commitment to establish protection and enactment of human rights law in its continent since 2007. Some experts say that its inability to perform meaningful actions is mainly attributable to its “non-interference policy”, a principle adopted by ASEAN with several unique characteristics that differs its practice with other organization practicing similar belief, mixed with a misguided application of implementation regarding “regional particularism”. This paper aims to understand the establishment of such principles’ implementation and how they influence the organization’s approach against violations of human rights happening under its member-states’ governments. Keywords: Human Rights Violations, Non-Interference, Regional Particularism Abstrak Pada zaman Duterte dan kebijakan pembunuhan di luar proses hukumnya, Aung Sang Suu Kyi dan penganiayaan sistemik etnik Rohingya, orang-orang Malaysia menolak ratifikasi Konvensi Internasional untuk Pemberantasan Diskriminasi Rasial (ICERD), dan berbagai peristiwa malang lainnya yang terjadi di berbagai daerah, Asia Tenggara menderita berbagai pelanggaran berat hak asasi manusia (HAM). Namun, sebagai organisasi yang memayungi sub-benua, tangan-tangan ASEAN sebagian besar terikat ketika menghadapi masalah-masalah yang berkaitan dengan wilayah mereka, meskipun berjanji untuk membangun perlindungan dan pemberlakuan undang-undang hak asasi manusia di benua itu sejak 2007. Beberapa ahli mengatakan bahwa ketidakmampuannya untuk melakukan tindakan yang berarti terutama disebabkan oleh kebijakan non-intervensi-nya, sebuah prinsip yang diadopsi oleh ASEAN dengan beberapa karakteristik unik yang berbeda praktiknya dengan organisasi lain yang mempraktikkan prinsip serupa, yang kemudian dicampur dengan implementasi “kekhususan regional” yang problematik. Artikel ini bertujuan untuk memahami pembentukan implementasi prinsip tersebut dan bagaimana hal itu mempengaruhi pendekatan organisasi terhadap pelanggaran hak asasi manusia yang terjadi di bawah pemerintahan negara-negara anggotanya. Kata Kunci: Kekhususan Regional, Non-Intervensi, Pelanggaran HAM